The Acehnese Folklore and Social Behavior - Gabriel Cristina (Journal of Aceh Studies, 2024)
The moral and cultural ideals portrayed in several Acehnese folktales are the main subject of this article's exploration of Acehnese folklore and social behavior. The goal of the study is to characterize the moral and cultural values that are ingrained in folklore, as well as its composition, transmission, social setting, and structure. Descriptive analysis is used in the research design, which is grounded in a qualitative method to analyze the data. The results highlight the wealth of regional knowledge and cultural values captured in the many Acehnese folktales that make up the data collection. The ramifications of these discoveries for the Acehnese community are explored in detail, with a focus on the function that folklore plays in passing down cultural traditions and values. The importance of maintaining and advancing Acehnese folklore as a source of social, cultural, and moral wisdom is emphasized in the article's conclusion.